Incidence of Mycotoxins (AFB1 and AFM1) in Feeds and Dairy Farms from Rio de Janeiro State, Brazil - Keller, Luiz Antonio Moura (2016)
Brazil has regions located at the largest dairy production and milk derivate industry concentration, supplying the major consumer markets, represented by São Paulo, Rio de Janeiro and Belo Horizonte Cities. The milk is the most important product of Brazilian agriculture, because it is always presents in daily diet. The aim of this research was evaluating the occurrence of mycotoxins in the feed of dairy cattle and the occurrence of AFM1 in milk under field conditions in farms from Rio de Janeiro State, Brazil. The results revealed that, total fungal counts was found in 67% of feed samples which exceeded the recommended limit recommended (1×104 UFC.g-1) and the incidence of AFM1 in all milk samples was 26.7% at concentrations ranging from 0.010 to 1.500 μg.L-1. The study revealed toxigenic fungi and their mycotoxins were present in feed intended for bovine feeding in Rio de Janeiro farms. Evaluations of mycotoxin levels are important to provide information so that the assessments of risk for animal feed and livestock environment can be done.